1991
DOI: 10.1007/bf00033209
|View full text |Cite
|
Sign up to set email alerts
|

Canopy gaps and establishment patterns of spruce (Picea abies (L.) Karst.) in two old-growth coniferous forests in central Sweden

Abstract: The spatial pattern of seedlings, saplings and canopy trees was studied in two spruce (Picea abies (L.) Karst.) forests in central Sweden. Canopy and forest structure were determined in five 0.25 ha plots. Life stage classes were distinguished on the basis of age and size distributions. Ripley's K-function (1977) was used to analyze the spatial patterns within each class. A random distribution of seedlings gave way to a more aggregated pattern on a small scale during the establishment phase. Saplings and sub-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
81
0
8

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(100 citation statements)
references
References 27 publications
11
81
0
8
Order By: Relevance
“…Gap-phase disturbances caused by death of individual trees or small groups of trees drive the mosaic structure and regeneration dynamics of old-growth forests in the absence of catastrophic disturbances (Hofgaard, 1993;Hytteborn and Packham, 1985;Kuuluvainen et al, 1998;Leemans, 1991;Liu and Hytteborn, 1991;Skvortsova et al, 1983).…”
Section: Disturbance Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gap-phase disturbances caused by death of individual trees or small groups of trees drive the mosaic structure and regeneration dynamics of old-growth forests in the absence of catastrophic disturbances (Hofgaard, 1993;Hytteborn and Packham, 1985;Kuuluvainen et al, 1998;Leemans, 1991;Liu and Hytteborn, 1991;Skvortsova et al, 1983).…”
Section: Disturbance Factorsmentioning
confidence: 99%
“…Aaltonen, 1919;Utkin, 1965;Verkhunov, 1970;Glagolev, 1975Glagolev, , 1976Dyrenkov, 1984;Zyabchenko, 1984;Fedorchuk et al, 1998;Shevelev, 1999 4. Bogushevsky, 1912;Ivashkevich, 1915;Sernander, 1936;Skvortsova et al, 1983;Dyrenkov, 1984;Hytteborn and Packham, 1985;Smolonogov, 1990;Leemans, 1991;Liu and Hytteborn, 1991;Hofgaard, 1993;Furyaev, 1996;Kuuluvainen et al, 1998;Fedorchuk et al, 1998;Volkov, 2003 * According to Figure 3. 201p16 Eurasian natural forest stands Ann. For.…”
Section: Management Implicationsmentioning
confidence: 99%
“…Lukkala 1946). Se perustuu kuusen kykyyn taimettua varjoisissa oloissa järeänkin puuston alla (Leemans 1991). Toinen syy on rahkasammalien edullinen vaikutus havupuun siementen itämiseen (esim.…”
Section: Johdantounclassified
“…It is often the result of larger or smaller natural gaps in the canopy of the stand (Leemans 1991). Geostatistical analysis in the Central Apennines found that yew occurred in patches and high density of mature yews suppressed regeneration (Piovesan et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important ecological factors, especially important for natural regeneration, is light conditions on the forest floor (Szwagrzyk et al 2001). The analysis of the horizontal spatial organisation of the forest allows us to study the relationships between younger and older trees (Leemans 1991;Szwagrzyk et al 2001;Szymura et al 2007). Spatial relationships between different naturally regenerating species in a mixed forest are particularly interesting because such knowledge could help us to explain the natural species change in the mixed forest.…”
Section: Introductionmentioning
confidence: 99%